KERANGKA PENGEMBANGAN PENDIDIKAN AGAMA KRISTEN (PAK) DENGAN PENDEKATAN TEORI FRIEDRICH W.A FROEBEL - Adolfina Putnarubun; Geneton Hully (Nusantara Hasana Journal, 2023)
Education is an important factor in creating human resources who can become individuals with good character, responsibility and honesty. Education takes place at every stage of human development, so that education must be implemented well from an early age. Education that takes place at the childhood stage has quite a few challenges. For this reason, various theories have emerged to see the possibility of appropriate strategies in developing education for children from an early age. One of the figures who had an influence in contributing his thoughts to building education for children at an early age was Friedrich W.A. Froebel, based on his own experience in facing various challenges while studying as a child, Froebel has an interest in creating a learning atmosphere that involves not only teachers, but also parents as children's first teachers. The contribution of Froebel's theory in the kindergarten school environment has had a very good impact, so that it can be a suggestion for scholars in formulating an appropriate curriculum, and in implementing the curriculum that is built it certainly involves both teachers and parents as colleagues in character formation. child. Regarding Froebel's theory, the goal that is intended to emerge is the creation of a framework of thought which will then become a reference for the development of Christian Religious Education, especially in schools. The method used is a qualitative method with a literature review approach.